Validity and Reliability Study for the Turkish Adaptation of the Generalized Anxiety Disorder-7 (GAD-7)Scale - (:unkn) unknown (TURKISH NEUROPSYCHIATRY ASSOC-TURK NOROPSIKIYATRI DERNEGI, 2013)
Objective: Our objective was to identify the validity, reliability and psychometric features of the Turkish adaptation of the Generalized Anxiety Disorder-7 (GAD-7) scale. Method: Patients who were diagnosed with 110 GAD patients and 112 healthy control subjects were included in this study. Three weeks after the initial administration, a certain group of the sample was administered the GAD-7 scale again. The principal components analysis for structural validity and confirmatory factor analysis were performed. Receiver operating characteristics (ROC) curve analysis was performed to identify the distinguishing feature. Positive predictive value, negative predictive value, positive and negative likelihood ratios were calculated at different cut-off levels. Results: The total scores for the GAD-7 scale-Turkish version in the GAD group were found to be statistically significantly higher than those in the control group. A significant correlation was observed between all items of the GAD-7 scale Turkish version that was found to have good internal consistency and intermittent administration. In the factor analysis performed for assessing the construct validity, the factor structure of the GAD-7 scale-Turkish version was found to be similar to the original form and the construct validity was found to be good. Good compliance to single factor structure was observed in the confirmatory factor analysis. The most acceptable cut-off point of the GAD-7 scale-Turkish version was found to be 8. Conclusion: The GAD-7 scale-Turkish version, similar to the original form, was found to have a high validity, reliability and good psychometric features in a clinical sample. The Turkish version of the GAD-7 scale was regarded as a useful screening tool. (Archives of Neuropsychiatry 2013; 50: 53-58)
Keywords: Generalized Anxiety Disorder-7 (GAD-7) scale-Turkish version; validity; reliability; PRIMARY-CARE; PREVALENCE; COMORBIDITY